O encontro entre o saber de referência dos estudantes e os conteúdos de ciências no currículo da educação de jovens e adultos - Del Monaco, Graziela (2014)
The Young and Adult Education (EJA) students are people who possess and produce knowledge built from their life experience and the school needs to hear, understand and use this knowledge in educational practices. Under this assumption, and aiming to contribute to discussions about the Science curriculum for EJA students, in view of the dialogue between school knowledge and students knowledge reference, this research was developed from the analysis of the students speeches, on the contents of Sciences, in elementary and high school, participating in a Young and Adult Education project in the Federal University of São Carlos (UFSCar). The research aimed to: identify the EJA students' views about scientific knowledge and popular knowledge; Analyze, from the students´ speech, the place of scientific knowledge and their knowledge reference in the EJA curriculum. In this study the education concept has been guided by Paulo Freire´s theoretical bases on problem and dialogical education and conceived EJA as the possibility for women and men to have access to education, a right denied when they were children and adolescents. The research data was constructed from the hermeneutics methodological and theoretical foundations and obtained by means of two press conferences (one mediated by films and the other by the analysis of the Science contents) and individual interviews. The students' speeches were analyzed in two chapters. One of them turned to the analysis of students' views on the scientific and popular knowledge and discussed the relationship between theory and practice, Science and popular knowledge. The other chapter carried out the analysis about the place of scientific knowledge and the students knowledge reference in the young and adult education curriculum. It discussed the subject specificities and their knowledge about school; the place that knowledge reference occupies in the curriculum and the place of Science contents and its relationship with students knowledge reference. For students the scientific knowledge has a very important place in the curriculum for being a content highly valued by them and they consider that the knowledge reference is a starting point to learn Science. Thus, an important specificity of the Science curriculum for young and adult education is the necessary link between school knowledge and the knowledge reference brought to school by students.